2017
DOI: 10.1088/1361-6528/aa6a9c
|View full text |Cite
|
Sign up to set email alerts
|

Integrating nanohybrid membranes of reduced graphene oxide: chitosan: silica sol gel with fiber optic SPR for caffeine detection

Abstract: Caffeine is the most popular psychoactive drug consumed in the world for improving alertness and enhancing wakefulness. However, caffeine consumption beyond limits can result in lot of physiological complications in human beings. In this work, we report a novel detection scheme for caffeine integrating nanohybrid membranes of reduced graphene oxide (rGO) in chitosan modified silica sol gel (rGO: chitosan: silica sol gel) with fiber optic surface plasmon resonance. The chemically synthesized nanohybrid membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…However, further refinement of the experimental results allowed the sensor to achieve a sensitivity of 2.47 nm/ppm. Kant et al [69] reported the development of an OFS for the detection of caffeine integrating reduced graphene oxide nanohybrid membranes on chitosan modified silica membrane. The sensor features a detection limit of 1.994 nM and operates over a concentration range between 0 and 500 nM with a RT of 16 s. Despite the wide spectrum of applications and publications reported, the development of OFS functionalized with OIH materials is still at an early stage.…”
Section: Applicationsmentioning
confidence: 99%
“…However, further refinement of the experimental results allowed the sensor to achieve a sensitivity of 2.47 nm/ppm. Kant et al [69] reported the development of an OFS for the detection of caffeine integrating reduced graphene oxide nanohybrid membranes on chitosan modified silica membrane. The sensor features a detection limit of 1.994 nM and operates over a concentration range between 0 and 500 nM with a RT of 16 s. Despite the wide spectrum of applications and publications reported, the development of OFS functionalized with OIH materials is still at an early stage.…”
Section: Applicationsmentioning
confidence: 99%
“…Further, SPR based fiber-optic sensors are used for the sensing and quantification of numerous chemicals and biomolecules of commercial and biomedical significance. 7,8,12,13 The importance of these sensors also stems from the fact that they facilitate multi-channel sensing significant from biological point of view. In that aspect, a cascaded channel fiber-optic SPR sensor has been reported for simultaneous detection of vitamin K 1 and heparin such that vitamin K 1 is sensed on first channel to monitor blood coagulation while the second sensing channel is specific to heparin required for the therapy.…”
Section: Opinionmentioning
confidence: 99%
“…Surface plasmons are the in-phase oscillations of free electrons at the interface of a metal and dielectric, as indicated by a strong absorption at the resonance wavelength in a UV-Visible absorption spectrum [110][111][112][113][114][115][116][117]. The SPR band position depends on parameters such as size, shape, and polydispersity of nanostructures, even though it is the ability of rGO to otherwise enhance and control the loading and embedding of AgNPs, due to improved specific surface areas thought to be the reason for the divergence in the signal between the Ag and Ag-rGO samples [56]. Resonance wavelengths strongly depend upon the refractive index of the dielectric medium.…”
Section: Nanoparticle-impregnated Polyviscose Substrate Synthesismentioning
confidence: 99%
“…Treated substrates displayed high air stability and chemical inertia, via a reduced graphene oxide (rGO) protective composite, i.e., the formation of AgNP-rGO composites within substrates for increased loading and enhanced active coating longevity [53,54]. The performance of these composites was compared against solely AgNP-and rGO-impregnated fabrics, with the presence of rGO acting to stabilise and facilitate the loading and adhesion of AgNP nanostructures, which provides them with an improved specific surface area and subsequent improved performance [55,56]. Furthermore, leaching tests indicate enhanced and prolonged adhesion such that, even after accelerated washing cycles, the novel composites still showed high silver loading and high bactericidal efficacy over six hours of treatment, for the optimised composites.…”
Section: Introductionmentioning
confidence: 99%